Analyses of entropy generation in micropolar liquid using overlapping multi-domain spectral quasilinearization method - Tantumita Das; Musawenkhosi Patson Mkhatshwa; Rajib Gope; Sabyasachi Mondal (Heliyon, 2023)
In this article, entropy generation on Micropolar fluid through a perpendicular hot sheet is studied. The governing equations of the mathematical model of this article will transfer to non-dimensional system of ordinary differential equations by similarity transformations. This system of non-dimensional ODEs will be solved by a newly developed spectral collocation method. The dimensionless mathematical calculations are handled through utilizing the spectral quasilinearization method (SQLM) along with the concept of overlapping grids. Condition numbers, residual error and solution error norms estimations are provided to appraise accuracy, convergence and the stability of this numerical method. Using the overlapping multi-domain (M-D) approach has been found to produce most accurate, stable and convergent solutions when contrasted to the single-domain (S-D) technique. The outcomes are displayed and depicted graphically and through tabular forms. The effects of different non-dimensional parameters on flow, temperatures, concentration and entropy generation are studied. The accuracy of the numerical method has been checked through comparison with previously published articles and error analyses test.